Patient reported outcomes in randomized controlled cancer trials in advanced disease: a structured literature review. Issue 6 (2nd June 2016) - Weingärtner, V.; Dargatz, N.; Weber, C.; Mueller, D.; Stock, S.; Voltz, R.; Gaertner, J.
ABSTRACT: Introduction: In advanced cancer quality of life (QoL) is the most important goal of care. It is measured by patient-reported-outcomes (PRO). This structured review evaluated how randomized controlled trials (RCTs) on anti-cancer therapy in advanced cancer reported PRO. Methods: Search was performed in MEDLINE via PubMed for RCTs with median patient survival of ≤2 years. Reporting was rated with the Consolidated Standards of Reporting Trials (CONSORT) PRO extension. Results: Of 370 retrieved publications, 117 were eligible, but only 30/117 (26%) reported PRO. QoL was most frequently measured (29/30). On average, 4.4 (SD 2.5) of the 14 CONSORT items were met. Conclusion: PRO are insufficiently reported in advanced cancer trials. Yet, this is paramount to enable an informed and patient-oriented decision making process.